From Ritual to Cultural Tourism: Repositioning Seblang in the Narrative of Banyuwangi City - Efendi, Irwan; Saputra, Diki Wahyu; Wulandari, Saskia (SINGOSARI: Jurnal Perkumpulan Prodi Pendidikan Sejarah Se-Indonesia (P3SI) Wilayah Jawa Timur, 2025)
This study examines the transformation of the Seblang ritual in Banyuwangi from a sacred practice to a strategic cultural tourism asset. The Seblang tradition, as one of the cultural heritages of the Using community, has undergone a significant repositioning in the narrative of Banyuwangi city's image development. This research was conducted in an in-depth and direct manner, through observation, intensive interviews, and documentation collection in Olehsari Village, Glagah District. The results of the study indicate that the repositioning of Seblang as part of city branding has succeeded in balancing the preservation of sacred values ​​with the development of the tourism economy. This phenomenon shows how a local tradition that used to be only a village cleaning and ward off disaster ceremony has now transformed into a dynamic part of life, as well as a symbol of regional pride that attracts the attention of domestic and foreign tourists. This transformation does not eliminate the spiritual essence of the ritual, but instead strengthens its existence through wider recognition and appreciation, while also providing a positive impact on the local economy and Banyuwangi's image as a cultural tourism destination.